Role of Sacrificial Meat Packaging and Distribution for Quality of Life Improvement - Wahab, Siti Norida; Othman, Norashida; Atan, Rosli; Ab Talib, Mohamed Syazwan (Environment-Behaviour Proceedings Journal, 2025)
This study investigates the role of sacrificial meat logistics in enhancing consumer trust and improving quality of life, with a focus on underserved communities. Using a survey of 328 respondents, the research examines the impact of packaging innovations, distribution systems, halal logistics, and religious compliance. Structural model analysis reveals that packaging, distribution, and halal logistics significantly enhance consumer trust, which mediates quality of life improvement. Religious compliance, while culturally essential, showed no direct impact. The findings contribute to halal logistics literature, emphasizing trust’s centrality. Practical implications include adopting advanced packaging, cold-chain systems, and awareness campaigns to optimize sacrificial meat distribution.